The Application of Peer Tutorial Method in the Maximum Mastery Efforts for Social Research Methods in Study Program IAP FISIP UMSU - Amrizal, Dedi; Yusriati, Yusriati (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
This research is intended as a reference for the learning system of social researchers in the Faculty of Social Sciences Political Science (FISIP), especially the Public Administration Study Program (IAP) so that they are better in learning. Monotonous conditions and the low arrest of students in important subjects such as the Social Research Method (MPS) make researchers interested in offering a new learning method by the name of a peer tutor who prefers activeness between smart students and those who are less smart to get together actively discuss and prepare course material offered. The results showed that the Peer Tutor learning method has succeeded in increasing student mastery to a better level if it cannot be said to be maximized through increasing student participation in learning and mastery of MPS material. This can be shown by the increased activity of students in terms of group work and discussions between groups conducted and the value of the pretest and posttest taken. Students have the spirit of dancing and perfecting the material given by lecturers, discussing preparing the best powerpoints, they also have the courage to ask and answer questions, discuss and work together with fellow group members to make powerpoints and present in front of the class. Increased mastery of MPS material can be seen from the ability to answer questions at the time of discussion and the acquisition of students' values before being given action after being given. The increase occurred also from cycle one to cycle two. In addition, these peer tutors provide activeness to students from preparing material in limited discussions in their respective groups and after getting the opportunity to present their work and help other groups defend their arguments in inter-group discussions. This method can be used as an alternative mastery of MPS material for future IAP students. Finally the researcher would like to thank all those who have helped with this research process.